Science Learning with SSI Context Based on Direct Learning to Improve the Ability to Make Inferences and Think Logically - Almasari, Intan Salsabila; Fadly, Wirawan (Journal of Natural Science and Integration, 2024)
This research aims to determine the effect of learning methods on participants' logical thinking abilities and learning outcomes. A quasi-experiment was used with a sample size of 63 grade 7 students from one of the junior high schools in Ponorogo and treatment for 1 month to achieve this goal. The analytical data used were questionnaires before and after treatment, interviews, and pre-test and post-test summative assessments. The analysis technique used is conventional calculations to show the percentage of logical thinking ability with high, medium, and low categorization. Furthermore, the summative assessment results of the independent T-test and N-gain test with software analysis and the Cohen Size Effect Test aim to measure the effectiveness of the learning method. The results of the research concluded that the Direct Learning method applied to the experimental group increased students' logical thinking abilities on the indicator of making conclusions by 27% and was considered more effective by 14% compared to the control class which used conventional methods. As an example, the Direct Learning method based on the SSI context to improve students' logical thinking abilities is studied in more depth and applied according to students' potential. In this case, it will be useful in increasing understanding of science learning.Keywords: make inferences, direct learning, logical thinking, science learning, socio-scientific issues